Philippines Financial Sector Assessment Program : Climate Change and Environmental Risks and Opportunities - Regelink, Martijn G.J. (World Bank, Washington, DC, 2021)
The Philippines’ financial sector is highly vulnerable to climate risks. The country has high exposure to natural hazards (typhoons, landslides, floods, droughts, volcanic eruptions), strong dependence on a climate-sensitive agricultural sector, and vast coastlines where all major cities and the majority of the population reside. Significant systemic vulnerabilities can materialize if large natural disasters affect the capital region. In addition to physical risks, Philippine banks can also be exposed to transition impacts, that is, risks that emerge during the transition towards a more sustainable and carbon-neutral economy. Philippine supervisory authorities should build capacity to better understand and manage climate risks and foster transparency. At the same time, there is opportunity for deepening financial markets for green growth, by addressing several market and institutional barriers. With limits in public spending, there is great need, but also a significant opportunity for the private sector to contribute to green inclusive growth, including finance for climate resilience and mitigation efforts.